Notes on the genus Paracyriothasastes Breuning, 1978 (Coleoptera: Cerambycidae: Lamiinae: Lamiini) - Huang, Gui-Qiang; Zhao, Xin-Xia; Yan, Kai; Li, Song; Zhang, Gui-Mei (Zootaxa, 2020)
The monotypic genus Paracyriothasastes Breuning, 1978 was established for Cereopsius marmoreus Pascoe, 1857 from Malaysia. Uraechoides Breuning, 1981 was established for Uraechoides vivesi Breuning, 1981 also from Malaysia, and is currently composed of the type species and U. taomeiae Hayashi, Nara & Yu, 1995, the latter from China (Taiwan) (Tavakilian & Chevillotte 2020).